2020
DOI: 10.1111/ajd.13254
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and photoallergic contact dermatitis to chlorpromazine

Abstract: Chlorpromazine is known to produce both systemic phototoxic and photoallergic reactions. However, it may also cause photoallergic contact dermatitis and, albeit exceptionally, allergic contact dermatitis (ACD). We present a series of photoallergic contact dermatitis and ACD to chlorpromazine diagnosed at a tertiary centre cutaneous allergy unit between 1980 and 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Phenothiazines are known as a class of organic compounds that are considered to be representative drugs for inducing phototoxic reactions as well as PACD. 14,15 A recent study reported a series of cases of PACD caused by topical phenothiazines, widely used as over-thecounter (OTC) antipruritic drugs in France. 16 Chlorpromazine, which is a phenothiazine, led to PACD in the greatest number of patients, with 23.8% of the patients recruited reporting positive PACD reactions, but only 13.0% of those reactions were of current or past relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenothiazines are known as a class of organic compounds that are considered to be representative drugs for inducing phototoxic reactions as well as PACD. 14,15 A recent study reported a series of cases of PACD caused by topical phenothiazines, widely used as over-thecounter (OTC) antipruritic drugs in France. 16 Chlorpromazine, which is a phenothiazine, led to PACD in the greatest number of patients, with 23.8% of the patients recruited reporting positive PACD reactions, but only 13.0% of those reactions were of current or past relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Phenothiazines are known as a class of organic compounds that are considered to be representative drugs for inducing phototoxic reactions as well as PACD 14,15 . A recent study reported a series of cases of PACD caused by topical phenothiazines, widely used as over‐the‐counter (OTC) antipruritic drugs in France 16 .…”
Section: Discussionmentioning
confidence: 99%
“…4,21 Although chlorpromazine is not applied topically, manual handling of tablets containing chlorpromazine followed by sun exposure may cause PACD, as we observed in one patient and in previous studies. 13,19,22 Nevertheless, many reactions to promethazine and most reactions to chlorpromazine were non-relevant suggesting that even at this lower concentration (0.1% pet. ), these phenothiazines still cause possible phototoxic reactions, that need to be interpreted cautiously.…”
Section: Photopatch Test Resultsmentioning
confidence: 95%
“…Some published case reports and case series have shown the therapeutic benefits of IM gels 0.15% and 0.05% for treatment of the AGWs (Table 2). [5][6][7][8][9][10][11][12][13] IM gel 0.05% has been used successfully to treat the genital warts in the sensitive anatomic locations. 6 Several studies have reported the patients with genital warts at the corona of glans penis or meatus, and peri and intra-anal skin who were completely treated following application of the IM gel 0.05% for 1 to 2 weeks with no recurrence during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have reported the patients with genital warts at the corona of glans penis or meatus, and peri and intra-anal skin who were completely treated following application of the IM gel 0.05% for 1 to 2 weeks with no recurrence during the follow-up period. 6,10,11 Results of a small study on 17 adult patients (aged between 21 and 70 years old; 15 males, 2 females) showed that the complete clearance rate was equal to 94% (16/17) and no recurrence was reported up to 240 days of follow-up. 9 In another study, 11 of 15 (73.3%) patients with AGWs showed the complete clearance after application of the IM gel (0.15% or 0.05%).…”
Section: Discussionmentioning
confidence: 99%